(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The critical discourse analysis of the discourses on Iraqi identity in media representations since the invasion of Iraq in 2003, a period of deep sociopolitical turmoil and transformation, is the subject of this research. The problem, therefore, deals with the construction and reflection of media narratives about Iraqi identity within continuing conflict, sectarian strife, and foreign intervention. The first and primary objective is to see the ways these narratives have constructed, contested, and negotiated Iraqi identity over the last two decades regarding nationalism, sectarianism, and globalization. Based on a corpus of articles from established local and international newspapers, online news sites, besides social media platforms, the study analyses the linguistic usages, framing, and strategies of representation taken up with Iraqis and their experiences. The analysis is informed by Fairclough’s three-dimensional model of discourse analysis, in which text, discursive practices, and sociocultural contexts are analyzed. The key findings demonstrate how media discourse continuously shifts between constructing Iraqis as victims of violence and as strong agents of their own destiny, in a complex interplay of victimhood and agency. This also underlines huge tension between national identity and sectarian narratives within media discourse, which often underlines divisions at the same time as it calls for unity. Overall, these results emphasize the great importance of media in framing public views on Iraqi identity and point to the need for more nuanced representations that go beyond simplistic binary oppositions. This paper contributes to the broader discussion on identity formation in the conflict zone by animating critical media literacy as a means of understanding the potentials of representation regarding collective identity.